Dari Gang Sempit ke Sentra UMKM: Inovasi Corporate Social Responsibility dalam Pemberdayaan Masyarakat Urban - Rina Ekawati; Dadan Abdan Sakur; Ari Djanuar Prasetyo (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Urban space limitations and community economic empowerment needs present complex challenges in Corporate Social Responsibility (CSR) implementation in densely populated areas. This study aims to analyze the effectiveness of MSME empowerment programs through optimizing narrow alleys into productive economic centers in Duren Tiga Village, South Jakarta. Using mixed methods research with sequential explanatory design and CIPP evaluation model, the study involved 9 assisted MSMEs, PT PLN Puslitbang management, and related stakeholders during August 2024-July 2025 period. Results show that transformation of 200 m² narrow alley into Café Mini Forest successfully increased average MSME turnover by 67.9% and halal certification achievement by 88.9%. The program integrates